The integration of farmer participation approaches in cotton variety development for efficient selection, adoption, and production of new cotton varieties in Zimbabwe - Mare M; Chapepa B; Mubvekeri W; Kutywayo D (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The success of any breeding program rests upon the active involvement and participation of key stakeholders or technology recipients. Cotton (Gossypium hirsutum L.) is a versatile crop that is grown in most parts of the world, hence the need to involve different players in the process. Zimbabwe's national variety development program includes a "Client-oriented" research approach called "Participatory Variety Selection" (PVS) in the process. The process that involved the evaluation of different advanced cotton genotypes by farmers in different cotton growing areas included five advanced genotypes and one commercial variety popularly grown by farmers. These were grown in a Mother-Baby Trial arrangement. Through the integration of farmers' and researchers' selection criteria, the study sought to enhance the identification and selection of best-performing cotton genotypes under diverse growing conditions. The study established that farmers' preferred cotton attributes included large bolls (> 5g), uniform boll split (to avoid many picks), short interboll distance (many bolls per fruiting branch), uniform short height (1.0-1.2m), more bolls per plant (>30) and low pest damage (bollworms and Jassid). Through the use of these attributes, the farmers identified SN-96-5, 830-01-3, and 645-98-11 as their best performing genotypes through voting and Focus Group Discussions that were conducted where they recorded 206 votes, 130 votes, and 129 votes respectively. Total Seed Cotton Yield data from the farmer-managed plots (Baby Trial) and Researcher-managed (Mother Trial) were recorded and subjected to statistical analysis. The study results which revealed significant differences in the genotypic, environmental variance, and interaction (Table 5) (P<0.04, P<0.001, and P<0.035 respectively) identified genotype SN-96-5 as the best performing genotype. AMMI and GGE biplots also indicated that SN-96-5 was the most ideal, high-yielding, and fairly stable genotype. Therefore, SN-96-5 is recommended for release and commercial production in Zimbabwe.